Estimation the Amount of Heat Generated by LEDs under Different Operating Conditions - Andonova, Anna; Kim, Namyong; Vakrilov, Nikolay (Elektronika ir Elektrotechnika, 2016)
LEDs are not 100 % efficient at converting input power to light. Some of the energy is converted into heat and must be transferred to the ambient. Two approaches are used to assess the amount of heat generated by the LED - based on the luminous efficacy of radiation and a new one presented in the paper. To provide sufficient accuracy in thermal evaluations closer to the real operating modes for a specific LED module a new technique is developed. The aim is to evaluate the amount of heat generated during design phase of LED lighting. Experiments of LED modules are conducted to evaluate LEDs efficiency at converting input power to heat. For the heat dissipation study and thermal analysis of LED module are used non-contact temperature measurement using an infrared camera combined with computer aided thermal modelling and simulation. DOI: http://dx.doi.org/10.5755/j01.eie.22.2.8522